Biodiversity and Health Symposium Conclusions and Recommendations - World Bank (Washington, DC, 2012)
The paper reported that to increase the effectiveness of healthcare as well as to alleviate poverty in the poorest parts of the world, the symposium participants recommended urgent attention to three principles: 1. Success will only be achieved if both biological diversity and cultural diversity are conserved.; 2. Leadership must come from indigenous peoples/(local communities) in the use of traditional knowledge for broader health benefits; 3. International cooperation and partnerships are necessary to ensure safety and quality of traditional phytomedicines.